Forensic Dentistry
1 online resource (470 pages)
Keywords: The identification of unknown individuals and the estimation of age, race, and gender are among the chief functions of forensic dentistry. Other important applications include the investigation and analysis of bitemarks and oral injuries in abuse cases and evaluating, reporting, and testifying in civil litigation cases. Twelve years after the benchmark first edition of this book explored these topics, the long-awaited Forensic Dentistry, Second Edition offers a comprehensive update and revision of the material. Offering insight from many new contributors on the cutting edge of forensic science and odontology, this new edition expands the book’s scope to include a broader historical and theoretical analysis, a thorough assessment of the past decade’s developments, and a far-reaching projection of future trends. New topics in the second edition include: Forensic dental radiography Age estimation Jurisprudence and legal issues History of forensic dentistry Landmark cases, including September 11th and Hurricane Katrina In order for forensic odontology to continue to progress as a specialty of forensic science, there must be a consistent stream of new ideas and original and applied research. Heavily illustrated and enhanced with a 16-page color insert with additional photos, this volume captures the critical issues that confront today’s forensic dentist, explores the field’s limitations, and provides a window on the future of this crucial sector within the forensic identification science arena.